How to catch a unicorn - Wallace, Adam; Elkerton, Andy (Naperville, Illinois : Sourcebooks Jabberwocky, 2019)
"Can you catch the unicorn? You'll have to use your brain. So set your traps and prep your team to pet that rainbow mane!"--
Ages 4 and up.
Keywords: Unicorns -- Juvenile fiction; Zoo animals -- Fiction; Humorous fiction; Stories in rhyme; Picture books